AKSI PEDULI LINGKUNGAN UNTUK MEWUJUDKAN KOMUNITAS SEHAT DAN KEBERLANJUTAN BAGI MASYARAKAT PESISIR MANGROVE - Marshanda Yovianita Sukma Hernandi; Nik Amah (Surakarta Abdimas Journal, 2024)
The mangrove ecosystem has good biodiversity in the form of flora and fauna. Mangroves function in coastal areas as a habitat in sea waters. Mangroves have a major impact on nature and living things. One of the ecosystems in the coastal area is the mangrove ecosystem, likewise the Oesapa coast has a mangrove ecosystem, but the condition of the mangrove forest on the Oesapa coast has long been buried by garbage. The garbage found consists of three categories, namely garbage from coastal communities, tourists and nature such as tree branches. Plastic waste is a problem that needs attention because it can have a negative impact on the marine ecosystem and the environment around the coast. Reprocessing plastic waste is an effort to avoid environmental pollution by plastic waste and can minimize the risk of spreading diseases due to microorganisms contained in organic waste. The community can also sell the waste to get extra money. This activity gave an exciting and extraordinary impression to the participants of the Inbound PMM 2 Nusa Cendana University, and this mangrove coastal cleanup movement succeeded in increasing public awareness and concern in maintaining the cleanliness of the Oesapa mangroves.